The effect of cool-mist humidifier on concentration of air pollutants and indoor environmental conditions - Maryam Malekbala; Zahra Heydari; Seyde Fateme Mousavi; Zahra Arshian Far; Zeinab Khalilnezhad; Roohollah Rostami (Journal of Air Pollution and Health, 2025)
Introduction: Indoor air pollution poses significant health risks, given the substantial time individuals spend indoors. Cool-mist humidifiers have been proposed as a potential intervention for enhancing indoor air quality by influencing pollutant concentrations. This study investigates the effects of gas dissolution in vapor particles generated by a cool-mist humidifier on indoor air pollutants. Materials and methods: A controlled laboratory experiment was conducted within a 1 m³ insulated plastic chamber to monitor key parameters, including Carbon monoxide (CO), Carbon dioxide (CO₂), Oxygen (O₂), Total Volatile Organic Compounds (TVOCs), temperature, and Relative Humidity (RH). Pollutants were introduced using a lit candle and formaldehyde, and air quality was measured using a digital gas analyzer (CEM GD-3803) and a TVOC analyzer (QB2000N/T). Baseline pollutant levels without humidification were compared to levels observed with a cool-mist humidifier operating at various humidification rates (110–370 mL/h) over an 8-h period. Results: The results indicated consistent reductions in CO₂ and TVOC concentrations across all tested humidification rates, accompanied by increases in temperature and relative humidity. CO concentrations exhibited more variable behavior, with alternating increases and decreases over the testing periods. Conclusion: These findings underscore the potential of cool-mist humidifiers as an effective strategy for reducing indoor air pollutants, particularly CO₂ and TVOCs. This has meaningful implications for enhancing indoor air quality and protecting public health.